2020
DOI: 10.3390/s20247238
|View full text |Cite
|
Sign up to set email alerts
|

The Reliability and Validity of Wearable Inertial Sensors Coupled with the Microsoft Kinect to Measure Shoulder Range-of-Motion

Abstract: Background: Objective assessment of shoulder joint active range of motion (AROM) is critical to monitor patient progress after conservative or surgical intervention. Advancements in miniature devices have led researchers to validate inertial sensors to capture human movement. This study investigated the construct validity as well as intra- and inter-rater reliability of active shoulder mobility measurements using a coupled system of inertial sensors and the Microsoft Kinect (HumanTrak). Methods: 50 healthy par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 66 publications
(80 reference statements)
0
17
0
Order By: Relevance
“…Ryselis reported an overall increase in accuracy of 15.7%. A combination of a Kinect and several Inertial Measurement Units (IMUs) could also be used to reduce the upper limb position error by up to 20%, according to Jatesiktat et al [ 50 , 51 , 52 ]. Finally, a device-independent approach is to incorporate body constraints (such as human skeleton length conservation and temporal constraints) to enhance the continuity of the estimated skeleton [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ryselis reported an overall increase in accuracy of 15.7%. A combination of a Kinect and several Inertial Measurement Units (IMUs) could also be used to reduce the upper limb position error by up to 20%, according to Jatesiktat et al [ 50 , 51 , 52 ]. Finally, a device-independent approach is to incorporate body constraints (such as human skeleton length conservation and temporal constraints) to enhance the continuity of the estimated skeleton [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that upper limb angle measurements based on the Kinect sensor and other reference instruments, such as goniometers or wearable sensors, have a high degree of validity [ 16 , 22 , 40 ]. The authors Beshara et al [ 22 ] also compared measurements with a goniometer and claimed that the use of wearable inertial sensors in conjunction with Kinect v2 is a reliable and valid way to assess active shoulder flexion and abduction, with minimal measurement errors (2–4°), which represents high reliability. The results of this study show a significant validity of the measurements with the Kinect v2 sensor with an error of ±1° compared to the specialist’s measurements.…”
Section: Discussionmentioning
confidence: 99%
“…Several researchers have evaluated the reliability of the Kinect v2 system in the analysis of upper limb functionality and found significant measurement accuracy [ 16 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. The authors Cai et al [ 21 ] found that the mean square error of the shoulder joint angle (adduction and abduction) was less than six degrees between the Kinect v2 (Microsoft, Redmond, WA, USA) and Vicon (Oxford Metrics Group, Vicon Motion Systems Ltd., Oxford, UK).…”
Section: Introductionmentioning
confidence: 99%
“…Ryselis reported an overall increase in accuracy of 15.7%. A combination of a Kinect and several Inertial Measurement Units (IMUs) could also be used to reduce the upper limb position error up to 20% according to Jatesiktat et al [48][49][50]. Finally, a device-independent approach is to incorporate body constraints (such as human skeleton length conservation and temporal constraints) to enhance the continuity of the estimated skeleton [51].…”
Section: Smoothing Out Kinect Errorsmentioning
confidence: 99%